STUDY OF INFLUENCE OF BIOLOGICALLY ACTIVE SUBSTANCES OF SEEDS-DONORS ON GERMINATION, YIELD, SEEDLING VIGOR OF TOMATO FRUITS UNDER DROP IRRIGATION - P. M. Akhmedova (Овощи России)
The effect of pre-sowing treatment by extract of seeds-donor of different concentrations on germination, seedling vigor, and yield of tomato was shown. The seeds of different varieties of winter wheat, barley, oats, alfalfa, soybean, and maize were used as a seedsdonor of biologically active substances. It was found that these substances increased the seed germination and improved the seed vigor, plant development and product quality. This technology can be considered as a source of increasing in labour productivity and seed production.